Tropospheric ozone effects on chemical composition and decomposition rate of Quercus ilex L. leaves. - Baldantoni, Daniela; Fagnano, Massimo; Alfani, Anna (The Science of the total environment, 2011)
We determined the effects of tropospheric ozone on the chemical composition of Quercus ilex L. leaves and their decomposition, with a view to assessing the influence of ozone on nutrient cycling and the sustainability of Mediterranean holm oak forests. Forming one of the most widespread thermophilous vegetation communities in the area, Q. ilex is a dominant and widespread evergreen oak in the Mediterranean, where concentrations of tropospheric ozone are particularly high. The dynamics of carbon, nitrogen, lignin and cellulose concentrations were monitored for six months during the decomposition of leaves from plants subjected to controlled ozone exposure in open-top chambers. Ozone-exposed leaves, compared to unexposed leaves, showed no significant differences in C, N, lignin and cellulose concentrations prior to the incubation in mesocosms. However, during decomposition, leaves from plants exposed to ozone lost C significantly more slowly and showed a higher C/N ratio than unexposed leaves. Ozone exposure significantly slowed down the decomposition rate, indicating a negative effect of tropospheric ozone on nutrient cycling, which may reduce long-term sustainability of the holm oak forest.
Keywords: Air Pollutants; Air Pollutants: chemistry; Air Pollutants: metabolism; Air Pollutants: toxicity; Atmosphere; Atmosphere: chemistry; Carbon; carbon cycle; Carbon: analysis; Carbon: metabolism; Cellulose; Cellulose: analysis; Cellulose: metabolism; Decaying leaf composition; Holm oak leaves; Lignin; Lignin: analysis; Lignin: metabolism; Mediterranean area; nitrogen; nitrogen cycle; Nitrogen: analysis; Nitrogen: metabolism; Ozone; ozone exposure; Ozone: chemistry; Ozone: metabolism; Ozone: toxicity; Plant Leaves; Plant Leaves: chemistry; Plant Leaves: metabolism; Quercus; Quercus: chemistry; Quercus: metabolism

Remote estimation of carbon dioxide uptake by a Mediterranean forest - Garbulsky, Martín F.; Penuelas, Josep; Papale, Dario; Filella, Iolanda (Global Change Biology, 2008)
The estimation of the carbon balance in ecosystems, regions, and the biosphere is currently one of the main concerns in the study of the ecology of global change. Current remote sensing methodologies for estimating gross primary productivity are not satisfactory because they rely too heavily on (i) the availability of climatic data, (ii) the definition of land-use cover, and (iii) the assumptions of the effects of these two factors on the radiation-use efficiency of vegetation (RUE). A new methodology is urgently needed that will actually assess RUE and overcome the problems associated with the capture of fluctuations in carbon absorption in space and over time. Remote sensing techniques such as the widely used reflectance vegetation indices (e.g. NDVI, EVI) allow green plant biomass and therefore plant photosynthetic capacity to be assessed. However, there are vegetation types, such as the Mediterranean forests, with a very low seasonality of these vegetation indices and a high seasonality of carbon uptake. In these cases it is important to detect how much of this capacity is actually realized, which is a much more challenging goal. The photochemical reflectance index (PRI) derived from freely available satellite information (MODIS sensor) presented for a 5-year analysis for a Mediterranean forest a positive relationship with the RUE. Thus, we show that it is possible to estimate RUE and GPP in real time and therefore actual carbon uptake of Mediterranean forests at ecosystem level using the PRI. This conceptual and technological advancement would avoid the need to rely on the sometimes unreliable maximum RUE.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: carbon cycle; CO2 uptake; eddy covariance; Mediterranean forests; MODIS; primary productivity; radiation use efficiency; Remote sensing; Vegetation

Remote estimation of carbon dioxide uptake by a Mediterranean forest - GARBULSKY, MARTÍN F; Penuelas, Josep; Papale, Dario; Filella, Iolanda (Global Change Biology, 2008)
The estimation of the carbon balance in ecosystems, regions, and the biosphere is currently one of the main concerns in the study of the ecology of global change. Current remote sensing methodologies for estimating gross primary productivity are not satisfactory because they rely too heavily on (i) the availability of climatic data, (ii) the definition of land-use cover, and (iii) the assumptions of the effects of these two factors on the radiation-use efficiency of vegetation (RUE). A new methodology is urgently needed that will actually assess RUE and overcome the problems associated with the capture of fluctuations in carbon absorption in space and over time. Remote sensing techniques such as the widely used reflectance vegetation indices (e.g. NDVI, EVI) allow green plant biomass and therefore plant photosynthetic capacity to be assessed. However, there are vegetation types, such as the Mediterranean forests, with a very low seasonality of these vegetation indices and a high seasonality of carbon uptake. In these cases it is important to detect how much of this capacity is actually realized, which is a much more challenging goal. The photochemical reflectance index (PRI) derived from freely available satellite information (MODIS sensor) presented for a 5-year analysis for a Mediterranean forest a positive relationship with the RUE. Thus, we show that it is possible to estimate RUE and GPP in real time and therefore actual carbon uptake of Mediterranean forests at ecosystem level using the PRI. This conceptual and technological advancement would avoid the need to rely on the sometimes unreliable maximum RUE.
Keywords: carbon cycle; CO2 uptake; eddy covariance; Mediterranean forests; MODIS; primary productivity; radiation use efficiency; Remote sensing; Vegetation

Volatile organic compound emissions in relation to plant carbon fixation and the terrestrial carbon budget - Kesselmeier, Jürgen; Ciccioli, Paolo; Kuhn, Uwe; Stefani, Paolo; Biesenthal, Thomas; Rottenberger, Stefanie; Wolf, Annette; Vitullo, Marina; Valentini, Ricardo; Nobre, Antonio; Kabat, Pavel; Andreae, Meinrat O. (Global Biogeochemical Cycles, 2002)
A substantial amount of carbon is emitted by terrestrial vegetation as biogenic volatile organic compounds (VOC), which contributes to the oxidative capacity of the atmosphere, to particle production and to the carbon cycle. With regard to the carbon budget of the terrestrial biosphere, a release of these carbon compounds is regarded as a loss of photosynthetically fixed carbon. The significance of this loss for the regional and global carbon cycles is controversial. We estimate the amount of VOC carbon emitted in relation to the CO2 taken up, based on our own enclosure and micrometeorological flux measurements of VOC emissions and CO2 exchange within the Mediterranean area and the tropical rainforest in Amazonia and on literature data. While VOC flux estimates are small in relation to net primary productivity and gross primary productivity, the amount of carbon lost as VOC emissions can be highly significant relative to net ecosystem productivity. In fact, VOC losses are of the same order of magnitude as net biome productivity. Although we must assume that large amounts of these reemissions are recycled within the biosphere, a substantial part can be assumed to be lost into longer-lived oxidation products that are lost from the terrestrial biosphere by transport. However, our current knowledge does not allow a reliable estimation of this carbon loss.
Keywords: carbon cycle; volatile organic compounds (VOC)

Carbon dioxide efflux and pCO 2 in soils of threeQuercus ilex montane forests - Piñol, J; Alcañiz, J M; Rodà, F (Biogeochemistry, 1995)
Soil CO2 efflux and pCO2 in the soil atmosphere were measured during one year at three montane sites of Mediterranean sclerophyllous forests in NE Spain. Two sites were located in the upper and lower slopes of a small catchment in the Prades mountains (mean precipitation 550 mm year-'), and a third site was located on a lower slope in the Montseny mountains (mean precipitation 900 mm year-'). The three sites were similar in bedrock and vegetation, but differed in soil characteristics and water availability. Seasonal variation of CO2 efflux and soil pCO2 were affected by soil temperature and, to a lesser extent, by soil moisture. Annual mean soil CO2 efflux (considered as soil respiration) was similar at Montseny and at the comparably located site at Prades (83 ± 18 S.E. vs. 75 4 9 mg CO2 m - 2 hour- , respectively), and was highest at the Prades upper slope site (122 ± 22 mg CO2 m -2 hour-l). Despite those relatively similar CO 2 effluxes, mean soil pCO2 was much higher at both Prades sites than at Montseny. Soil pCO2 always increased with depth at Prades while maxima pCO2 at Montseny were often at 20-30 cm depth. A model based on gas diffusion theory was able to explain why soil pCO2 was much higher at Prades than at Montseny, and to reproduce the shape of the vertical profile of pCO2 at the Prades soils. Nevertheless, the model failed to simulate the soil pCO2 maximum found at 20-30 cm depth at the Montseny site. Model simulations using a time-variable CO2 production rate suggested that pCO2 maxima at intermediate depth could be the result of a transient situation instead of an equilibrium one.
Keywords: carbon cycle; Carbon dioxide; Mediterranean ecosystems; soil atmosphere; Soil respiration

Carbon dioxide efflux and pCO 2 in soils of threeQuercus ilex montane forests - Piñol, J.; Alcañiz, J. M.; Roda, F. (Biogeochemistry, 1995)
Soil CO2 efflux and pCO2 in the soil atmosphere were measured during one year at three montane sites of Mediterranean sclerophyllous forests in NE Spain. Two sites were located in the upper and lower slopes of a small catchment in the Prades mountains (mean precipitation 550 mm year-'), and a third site was located on a lower slope in the Montseny mountains (mean precipitation 900 mm year-'). The three sites were similar in bedrock and vegetation, but differed in soil characteristics and water availability. Seasonal variation of CO2 efflux and soil pCO2 were affected by soil temperature and, to a lesser extent, by soil moisture. Annual mean soil CO2 efflux (considered as soil respiration) was similar at Montseny and at the comparably located site at Prades (83 ± 18 S.E. vs. 75 4 9 mg CO2 m - 2 hour- , respectively), and was highest at the Prades upper slope site (122 ± 22 mg CO2 m -2 hour-l). Despite those relatively similar CO 2 effluxes, mean soil pCO2 was much higher at both Prades sites than at Montseny. Soil pCO2 always increased with depth at Prades while maxima pCO2 at Montseny were often at 20-30 cm depth. A model based on gas diffusion theory was able to explain why soil pCO2 was much higher at Prades than at Montseny, and to reproduce the shape of the vertical profile of pCO2 at the Prades soils. Nevertheless, the model failed to simulate the soil pCO2 maximum found at 20-30 cm depth at the Montseny site. Model simulations using a time-variable CO2 production rate suggested that pCO2 maxima at intermediate depth could be the result of a transient situation instead of an equilibrium one.
Keywords: carbon cycle; Carbon dioxide; Mediterranean ecosystems; soil atmosphere; Soil respiration